2013
DOI: 10.1039/c3dt51010g
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor and bright white upconversion luminescence from rice-shaped lanthanide doped BiPO4 submicron particles

Abstract: In this paper, uniform rice-shaped lanthanide doped BiPO4 upconversion submicron particles have been successfully synthesized via a facile room-temperature co-precipitation reaction and subsequent calcination route. The morphology, phase transformation and upconversion luminescent properties of synthesized submicron particles (SMPs) were characterized by using different analytical techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), thermogravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Therefore, many scholars have focused on the search for utilizing visible light by doping with hybrid atoms and coupling with other low energy gap semiconductors. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Other effects have been made, such as metal elements doping [31][32][33][34] and surface noble-metal modification. E-mail: wangdj761118@163.com; yadxfufeng@126.com; +86- It is well known that the photocatalytic process involves the generation of charge carriers such as electrons and holes induced by light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many scholars have focused on the search for utilizing visible light by doping with hybrid atoms and coupling with other low energy gap semiconductors. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Other effects have been made, such as metal elements doping [31][32][33][34] and surface noble-metal modification. E-mail: wangdj761118@163.com; yadxfufeng@126.com; +86- It is well known that the photocatalytic process involves the generation of charge carriers such as electrons and holes induced by light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…ions, which suggests that the valence state of part Tm ions is changed in the fabrication process of Tm 3? -doped fibers (Wang et al 2013;Kim et al 2003a, b). Figure 6 shows the up-conversion emission spectrum of Tm 3?…”
Section: Resultsmentioning
confidence: 96%
“…-doped material under the excitation of a NIR laser. Up-conversion photoluminescence from the excitation of a NIR laser is compact, powerful, inexpensive, and commercially available (Wang et al 2013, Ei-Agmy et al (2003 demonstrated the visible and near-infrared up-conversion properties in Tm 3? -doped ZBLAN fiber under the excitation at 1064 nm.…”
Section: Introductionmentioning
confidence: 98%
“…Also, white and multicolor UCLNPs have attracted much attention due to their potential applications in backlight sources in color displays and security labeling. 18,19 It is well known that matrix selecting is an important factor to get desired UCL, in which various host materials, such as sulde, uorides, oxygenated compounds, can be used for UC emissions. [20][21][22] Among these, uorides are considered as excellent hosts because of their relatively lower cut-off phonon frequency and lower non-radiative relaxation.…”
Section: Introductionmentioning
confidence: 99%